Agama, Modernisasi, dan Teori Kritis: Sebuah Potret Pertautan - Prihantato, - (Unisia, 2016)
In the discourses of contemporary social and humanitarian sciences. Jurgen Habermas cannot be ignored. His works have been influential not only in social sciences and philosophy, but also in other sciences, including theology. In this context, theology of every religion maybe completed based on The Habermas paradigm, namely the theory of Communicative Action. This effort should be done as a dialog between theology and the development of contemporary science, so that theological statements can be expressed communicatively to the present peoples. Through the assistance of critical theories, religious institution together with theological apparatus should not be alienated from the experience of modern people. Theology should be as such communicative that it is reasonable for its proponents.